Estimates of nitrogen fixation by legume cover crops grown in young rubber plantations using 15N isotope dilution technique - Prasannakumari, P.; Joseph, Mercykutty; Jessy, M.D.; Philip, Annie (Journal of Plantation Crops, 2014)
15N Isotope dilution technique has been used to estimate the amounts of N2 fixed by leguminous cover crops, Pueraria phaseoloides and Mucuna bracteata grown in the inter-rows of immature rubber plantation, using Ipomoea batatas as the reference plant. The field experiment was conducted in the RRII farm during 2009, in an area planted with Hevea brasiliensis, clone RRII 105. The cover crops and the reference plant were established in separate blocks. For labeled urea application, micro-plots (1m x 1m) were established and 15N labeled urea, 5 atom % 15N excess, was applied @ 5 kg ha-1. After 45 days, the above ground biomass from the micro-plots was harvested, weighed and sub-samples were collected for determination of dry matter accumulation, N content and 15N enrichment. Micro-plot experiments were conducted thrice during the active growth period of the legumes and the reference plant, i.e., during June-July, August-September and October-November. Estimates of N2-fixation for P. phaseoloides ranged from 79.82 kg N ha-1 during June-July to 39.32 kg N ha-1 during October-November and averaged 58.1 kg N ha-1. Corresponding estimates for M. bracteata ranged from 83.95 kg N ha-1 during June-July to 57.03 kg N ha-1 during October-Nov and averaged 69.7 kg N ha-1. The study showed that both the cover crops fixed considerable quantities of atmospheric nitrogen and that N2 fixation by M. bracteata was higher than that of P. phaseoloides.